Rola mitów i mitologemów w kompozycji rytuałów na starożytnym Bliskim Wschodzie - Nowicki, Stefan (Uniwersytet Wrocławski. Pracownia Badań nad Tradycją Oralną, 2017)
The aim of this article is to present the ritual traditions that have been preserved in textual sources from the ancient Near East in the context of beliefs and myths, known from literary texts. As can be observed, texts regarding gods and heroes were closely connected with ritual compositions. At the foundations of this fact lies the conviction regarding the cyclical nature of the world. If a described action is revealed to be efficient once, the repetition of exactly the same steps brings exactly the same result. That is why the inclusion of the appropriate fragments of myths in the ritual guaranteed its effectiveness, as the whole action was nothing more than the reconstruction of the divine performance. The same action can be observed in the opposite direction in ancient Near Eastern myths we find descriptions of rituals known from strictly ritualistic compositions, but performed by different gods and goddesses. We consider how the existing stories were not universal, and thus could not be used for the purposes of any specific case, yet some of them were created for the sake of a particular ritual. Their structure was exactly the same as that of myth, and their role was to justify the objective and rationale of actions taken by exorcists, the efficiency of the ingredients and artefacts used, or to guarantee the planned result of incantations recited. Therefore, we may argue that no ritual could exist which did not include any mythical elements, as this would negate all assumptions regarding its potential effectiveness.
Keywords: myth; ritual; ancient Near Eastern religions; literary tradition